Brain electromagnetic activity and lightning: potentially congruent scale-invariant quantitative properties - Persinger, Michael A. (Frontiers in Integrative Neuroscience, 2012)
The space-time characteristics of the axonal action potential are remarkably similar to the scaled equivalents of lightning. The energy and current densities from these transients within their respective volumes or cross-sectional areas are the same order of magnitude. Length–velocity ratios and temporal durations are nearly identical. There are similar chemical consequences such as the production of nitric oxide. Careful, quantitative examination of the characteristics of lightning may reveal analogous features of the action potential that could lead to a more accurate understanding of these powerful correlates of neurocognitive processes.